BIM 4D–7D as the basis for integrated lifecycle management of industrial and civil construction projects - Stepaniuk , R. (Ways to Improve Construction Efficiency, 2024)
The article explores digital modernization as a systemic response to the global challenges faced by the organization of industrial and civil construction in the context of technological transformation, market dynamics, and increasing demands for efficiency, environmental sustainability, and management quality. It is established that modernization encompasses technological, organizational, and managerial levels and involves the implementation of BIM, Smart Site technologies, IoT, digital twins, predictive analytics, and artificial intelligence tools. The necessity of forming a seamless digital vertical from design to construction and further to operation is substantiated. Particular attention is paid to the development of BIM 4D–7D systems as instruments for integrated lifecycle management of construction projects. The article presents practical examples of the application of these technologies in Finland, the United Kingdom, and Germany. Indicative benchmarks of digital transformation are identified, including the level of document workflow automation, data integration, digital literacy of personnel, and analytics maturity indicators. The article also adapts the CMMI process maturity model to the construction development sector, describing five levels of organizational process coherence — from chaotic to optimized. For each level, specific indicators and digital tools are defined. A development roadmap for process maturity is proposed, incorporating strategic priorities and digital management platforms. It is concluded that digital modernization is interdisciplinary in nature and requires synchronized changes in technical, managerial, and regulatory environments, acting as a key factor in ensuring flexibility, resilience, and competitiveness of construction enterprises in the digital era.